Kairos Sebagai Golden Moment Orang Percaya - Daniel Sutoyo (Sekolah Tinggi Teologi Torsina Surakarta, 2018)
Kairos is a word used which been distinguished from others Greek’s words that explaining about time. In human life, time is a most important thing, because every occurrence is related to the time. Every people yearn the happiest times like achievement and successful, such a golden moment in life. Kairos could be understood as a golden moment for every people. This article aimed to explain the meaning of kairos according to its usage in the New Testament’s context and the implication to the believers today. This is a research that used a word analysis method, namely the word of kairos. The conclusion is, that kairos is a form of a word using for the time which could be understood as a moment that every people could achieve what they were expected.AbstrakKairos merupakan salah satu bentuk waktu yang dijelaskan dari bahasa Yunani untuk membedakan dari bentuk waktu secara umum. Waktu dalam kehidupan manusia merupakan hal yang sangat penting, karena setiap hal terjadi berkaitan dengan waktu. Setiap orang merindukan adanya saat-saat yang menyenangkan, seperti pencapaian dan keberhasilan, semacam masa keemasan dalam hidupnya. Kairos dapat dipahami sebagai bentuk masa keemasan bagi setiap orang. Artikel ini bertujuan untuk menjelaskan makna kairos secara konteks Perjanjian Baru dan implikasinya bagi orang percaya di masa kini. Ini adalah sebuah penelitian yang menggunakan metode analisis kata, yaitu tentang waktu. Kesimpulannya, kairos adalah sebuah bentuk waktu yang dapat diartikan seperti kesempatan agar setiap orang dapat mencapai sesuatu yang diidamkan.